The application of medicinal plants in the local community of Gantara Forest, Southeast Sulawesi, Indonesia - NURNANINGSIH HAMZAH; HUSNA HUSNA; RUSLIN RUSLIN; MUHAMMAD ARBA (Society for Indonesian Biodiversity, 2022)
Abstract. Hamzah N, Husna, Ruslin, Arba M. 2022. The application of medicinal plants in the local community of Gantara Forest, Southeast Sulawesi, Indonesia. Biodiversitas 23: 6557-6563. The local community around Forest Management Unit (FMU) Gantara (Gantara Forest) has traditionally utilized medicinal plants, especially people in Liwu Metingki Village of Muna District, Southeast Sulawesi Province, Indonesia, yet the least information on its application has been recorded. This study investigated the traditional application of medicinal plants by the local community nearby Gantara Forest, specifically Liwu Metingki Village. Exploratory research was implemented using the multi-method approach of field observation and a semi-structured interview with 17 traditional practitioners living around Gantara Forest. The study successfully collected and identified 34 potential medicinal plants in 20 families to treat 21 diseases. Most plants have a habitus of the tree (39%), which 67% of the local community apply as traditional herbs. Boiling has become the most popular practice in using medicinal plants of the local community (45%) to obtain benefits from the plants against internal diseases (37%). This finding demonstrates the vital role of sustainable management of Gantara Forest for human health. With this finding, the community is strongly expected to understand the significant role of medicinal plants, so they can attempt to protect the plants by, for example, planting them in their yards.